IMPACT OF SOCIO-ECONOMIC STATUS ON DETERMINANTS OF MEDICAL CAREER - Hafeez, Aamir; Shah, Syed Manzoor Hussain (Journal of Ayub Medical College Abbottabad, 2016)
Background: Research on determinants of Medical profession has established some constant factors with universal impact and appeal. However, the dramatic changes in the dynamics of medical profession and medical education over the past years have necessitated a revisiting of the established conclusions. The knowledge of impact of economic status on these determinants would pave way to greater interest and research on the subject, especially in Hazara Division where it is practically non-existent. Methods: This exploratory research followed deductive-inductive approach and was conducted upon 550 respondents from four public and private colleges in Hazara Division. Extensive study of related literature yielded 20 broad determinants of medical career. Pre-research pilot testing verified the reliability of a self-designed instrument. The data collection method adopted was a single shot survey. Personal data of respondents was collected during administration of the instrument. The sample was extracted through systematic random sampling technique giving due weight to proportional representation of each college as well as to the gender distribution. Results: The results revealed a significant difference in the impact of reassuring social perceptions and social status and prestige of medical profession between upper middle class and lower middle class. The results also showed that the students of upper middle class faced significantly greater domestic and familial pressure to enter the medical profession than those from lower middle class. Conclusion: The findings showed that the upper middle class is under greater influence of societal forces and wider impressions about the medical profession. The students hailing from upper middle class enter the Medical career motivated by urge for social status and prestige and are most compelled by domestic and familial pressures to enter medicine. Keywords: Medical career; Career choice; Determinants; Economic status